2002
DOI: 10.1149/1.1481529
|View full text |Cite
|
Sign up to set email alerts
|

Poly-Si Thin-Film Transistors Crystallized by Electron-Beam Annealing

Abstract: We have investigated an alternative electron-beam crystallization method for poly-Si thin-film transistor application. In contrast to the high crystallization temperature and long duration of conventional furnace crystallization, electron-beam crystallization could be performed at a low thermal budget even without substrate heating. It also provides better device characteristics than conventional furnace annealing, including smaller threshold voltage, higher mobility, smaller subthreshold swing, and larger I O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is reported that the exposure of various materials to electron beams has been shown to modify their crystallinities and improve their electrical properties [33][34][35]. Although the electrical properties of ZnO films can be improved by annealing processes [36,37], this entails more processing time in ramping the temperature up and down.…”
mentioning
confidence: 99%
“…It is reported that the exposure of various materials to electron beams has been shown to modify their crystallinities and improve their electrical properties [33][34][35]. Although the electrical properties of ZnO films can be improved by annealing processes [36,37], this entails more processing time in ramping the temperature up and down.…”
mentioning
confidence: 99%